INVESTING IN CASH FLOWS AND FIXED ASSETS - Ahmed Imad Jawad Alradhi (Galaxy International Interdisciplinary Research Journal, 2023)
Companies rely on their internal cash to finance their investment projects in the event of insufficient financing through capital markets. Investment to cash flows is an indicator to measure the amount of changes in capital expenditures per unit change in the company’s cash flows. This means that fluctuations in the volume of investments versus changes in cash flows express the concept of sensitivity of investment cash flows. If available internal funds are insufficient for investment activities, the company will use external funds to make further investments. Ease of obtaining capital from external sources makes the company’s investment activities less dependent on internal capital. In the field of corporate finance, the level of investment activity depends on the presence of local capital. Investment and financing are important issues in corporate financial management.